Primary sources in History Teaching in Latin América and Spain. Reflections from a global view - Sáez-Rosenkranz, Isidora (2024)
In this paper two related objectives are proposed. On the one hand, to know what has been published on primary sources in history teaching in Latin American Spanish-speaking countries and in Spain and, with those results as a baseline, to discuss some challenges for History Teaching academic discipline. To this end, firstly it was made an identification and quantification of works recognized by Publish or Perish tool and the production of these publications was analyzed descriptively. It was found that academic concerns about the question of sources on both sides of the Atlantic are different and are linked to the trajectory of the disciplinary field. From here, the paper reflects on the role of sources in the construction of historical knowledge promoted in schools, the role of the teacher in this construction and the ethical precautions to be considered.